Efficacy of chalcone and xanthine derivatives on lipase inhibition: A systematic review. (25th November 2019) - Tam, Dao Ngoc Hien; Mostafa, Esraa Mahmoud; Tu, Vo Linh; Rashidy, Asmaa Ibrahim; Matenoglou, Evangelia; Kassem, Mahmoud; Soa, Dang Thi; Bayumi, Amera; Emam, Hagar Ehab Said; Tran, Linh; Dat, Truong Van; Huy, Nguyen Tien
Abstract: Losing weight has significant impact on chronic disease management. Orlistat, a lipase inhibitor, has alternative effect for weight controlling. To find more candidates, we conducted a review of chalcone and xanthine derivatives regarding their anti‐lipase activity. Eight databases were searched including PubMed, Scopus, Web of Science (ISI), Virtual Health Library (VHL), System for Information on Grey Literature in Europe (SIGLE), Global Health Library (GHL), EMBASE, and Google Scholar in August 2018. We found chalcone scaffold was more effective on lipase inhibition than xanthine scaffold. Among 19 investigated chalcones, only isoliquiritigenin and licuroside demonstrated an effect on preventing weight gain and increase in the total cholesterol and total triglycerides aside apart from their high activity on inhibiting lipase. Effect and type of inhibition of individual chalcones differed depending on their structure. In addition, very few studies investigated xanthine compounds and their activities were inconsistent. We suggest more studies investigate the ability of chalcones and modifying their structure to find out other compounds with higher efficacy. Abstract : Our study found that compounds with chalcone scaffold are higher effective than xanthines. Amongst them, three chalcones, namely isoliquiritigenin, morachalcone A, methylenebisphloretin, are the most potential candidates with IC50 values <10 µM. They could be non‐competition inhibitors or mixed‐type competitors. Some chalcones could make bonds with pancreatic lipase which can be a model for further studies in drug design. Compound with low absorption in the body could exhibit more effective than the others.